An efficient experimental approach for high-throughput discovery of novel Ti-based shape-memory alloys - Yuxin Song; Sheng Xu; Toshihiro Omori; Ryosuke Kainuma (Journal of Materials Research and Technology, 2024)
β-Ti shape-memory alloys, that show shape-memory effect or superelasticity owing to thermoelastic martensitic transformation, have potential for various applications. Herein, we propose an experimental approach for the efficient and high-throughput discovery of Ti-based shape-memory alloys with new compositions. We employed a diffusion couple composed of Ti–4.5Cr (at%) and Ti–30Al–4.5Cr (at%) alloys, and combined techniques of microstructure characterization and micro-Vickers hardness testing to uncover the surface relief attributable to martensitic transformation, correlating with varying Al concentration. By coupling with the observation of abrupt decline in the Vickers hardness and stress-induced martensitic transformation near the indent, a β-phase Ti alloy with a new composition of Ti–17Al–4.5Cr (at%) was successfully found, and excellent shape-memory effect was demonstrated. The integration of the diffusion couple, hardness test, and microstructural analysis provides a robust framework for the accelerated development of new Ti-based shape-memory alloys.